Bioactive substances and therapeutic potential of camellia oil: An overview. (October 2022) - Li, Zhe; Liu, Ao; Du, Qing; Zhu, Weifeng; Liu, Hongning; Naeem, Abid; Guan, Yongmei; Chen, Lihua; Ming, Liangshan
Abstract: Camellia oil (CO) extracted from mature camellia seeds has gained considerable attention for nutritional and medicinal applications because of its excellent biological activities. The main bioactive components present in CO are fatty acids, vitamin E, squalene, phytosterol, flavonoids, and polyphenols. Numerous studies have demonstrated the potential health benefits of CO, including regulation of lipid and blood pressure levels, inhibiting tumor growth, protecting against Alzheimer's disease, and having anti-asthmatic, anti-diabetic, anti-inflammatory, antioxidant, and antibacterial properties. However, the molecular mechanisms of the bioactive substances present in CO are still unclear, limited, and no adequate data has been gathered regarding their health effects. Due to the rapid growth of biological applications of CO, it is necessary to provide an updated review of the current research progress in this area. In this review, the advancements in the compositions and structures of CO are discussed in detail. Additionally, recent research related to CO's therapeutic potential is discussed. In conclusion, a perspective on the prospects and challenges of CO in biomedicine is also provided. A mechanistic understanding of the chemical compositions and multifunctional properties of CO can provide the basis for the further exploitation of CO in medicine and functional foods. Graphical abstract: Image 1 Highlights: Camellia oil has both nutritional and medicinal properties. Bioactive substances in camellia oil have been systematically analyzed. Camellia oil is a potential candidate for therapeutic use. Systematic studies on molecular mechanisms of camellia oil are needed.